Peran Organisasi Perempuan Sidoarjo dalam Merespon Kekerasan Terhadap Perempuan dan Anak di Sidoarjo - Nurul Asiya Nadhifah (State Islamic University (UIN) of Sunan Ampel, 2018)
This article is the result of the research on the role of the women's organizations in Sidoarjo in responding to violence against women and children in Sidoarjo. The women's organizations in Sidoarjo referred to in this study are Fatayat of NU Branch Sidoarjo, Muslimat of NU Branch Sidoarjo, Regional Administrators Aisyiyah of Sidoarjo, Student Association of Nahhdlatul Ulama (IPPNU) Branch of Sidoarjo and Nasyi'atul Aisyiyah of Sidoarjo. Domestic violence is any act against a person, especially women, which results in physical, sexual, psychological misery or suffering resulting from neglect of the household, including threats to do illegal acts of deprivation or deprivation of liberty within the household. The results of the study concluded that Fatayat of NU, Muslimat, Aisyiyah, Nasyi'atul Aisyiyah and IPPNU had an important role in participating and handling cases of violence against women and children that occurred in Sidoarjo. They realize that women's organizations must respond to community development and needs. They participated with the government in dealing with victims of violence against women and children in Sidoarjo. The handling of cases of violence against women and children is not only in legal protection, but trauma healing assistance to victims is also done so that victims can return to their activities as before the violence occurred.